A formação do professor de um curso de inglês para professores da rede pública: reflexão crítica sobre o contexto criado para ensino-aprendizagem - Capella, Leandro (2015)
This research focuses on a lesson plan as well as the practices and actions that occurred during this lesson in a course of teaching-learning of English language for public school English teachers. In a process of critical reflection, the researcher-teacher interprets and analyzes data produced in the planning and in the audio recording of the lesson in focus to a) investigate which theoretical bases of language and foreign language teaching-learning approaches permeated the planning and the organization of such lesson; b) examine how the organization of language and contexts took place in order to support the relations that aimed at students' language development; c) critically analyze and propose suggestions for transformation in both planning and organization of this lesson. Providing that, this research has three major theoretical foundations Cultural-Historical Activity Theory (CHAT) initially developed from the studies of teaching-learning of Vygotsky [1930-1934]; different views of language learning and the most popular methods, methodologies and approaches of teaching-learning foreign languages; Critical Reflection (FREIRE, 1970; SMYTH, 1929). The results of the analysis and interpretation of the data point to a structuralist view of language and behaviorist teaching-learning crusted in both actions and thinking of the researcherteacher in opposition to "whom he actually believed to be". Based on these comprehensions, by critically reflecting upon his actions, the researcher-teacher makes suggestions for issues that could have permeated the planning and the organization of the lesson concerning teaching-learning of English through collective collaboration among all participants